BRCA 1 and 2 gene expression in bitches (Canis lupus familiaris) mammary tumors and its association with clinical-pathological parameters (Gaceta de Ciencias Veterinarias, 2023)
Breast cancer susceptibility genes 1 and 2 (BRCA 1 and 2) are tumor suppressor genes responsible for repairing damaged DNA. Investigating the expression levels of BRCA 1 and 2 and associating it with the expression of proteins involved in breast cancer in dogs will be very useful for advances in the study of breast cancer in both women and dogs. The objective of the present study was to determine the expression, through real-time PCR in neoplastic mammary tissue, of the BRCA 1 and 2 gene and its association with clinical-pathological parameters in Cocker, Poodle and crossbred bitches. Real-time PCR was performed and the level of expression of BRCA 1 and 2 normalized with β-actin was quantified through the 2 Delta Delta CT method. It was observed that BRCA 1 is not associated with clinical-pathological parameters and is not an indicator of malignancy in Cocker, Crossbred and Poodle bitches. BRCA 2 was found in low expression in the mammary tumors of Cocker and Mestiza bitches, and is associated with ERα positivity. It is concluded that the expression of BRCA 1 and 2 in the mammary tumor is heterogeneous by individual. Taking into account the family inherited nature of the gene in the development of breast cancer, its study can provide more information in those races with a clear predisposition to the disease. Keywords: BRCA 1, BRCA 2, mammary tumor, bitches, qPCR.
Keywords: BRCA 1; BRCA 2; mammary tumor; bitches; qPCR